Fluid Simulation of a Cusped Field Thruster. Issue 7 (27th May 2015) - Liu, H.; Wu, H.; Meng, Y.; Yang, S.; Zhang, J.; Yu, D.
Abstract The cusped field thruster is a kind of newly developed electric propulsion device. The electric field at the channel exit and the low frequency oscillation were measured by former experiments. While the formation mechanism of them have not been fully interpreted yet. Through studying two distinguishing typical electron paths in the thrusters, a fluid model is built up along two electron paths, and then the model is completed by synthetically analyzing the effect of two electron paths. Time‐averaged electric potential distribution, anode current oscillation curve and time‐synchronized atom density and ion density distribution are obtained by simulation. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)